Charge neutral crystal field transitions: A measure of electron–phonon interaction. (December 2019) - Kumar, Anil; Sati, Aanchal; Mishra, Vikash; Warshi, M. Kamal; Kumar, Rajesh; Sagdeo, P.R.
Abstract: We report a study on the charge neutral crystal field (d–d) transitions and their possible correlation with coupling between continuum states above the optical band gap in pure and irradiated PrFeO3 . For this purpose, room temperature optical absorption spectroscopy and Raman spectroscopy measurements were carried out. It was observed that width (Wd–d ) and relative intensity (ID ) of d–d transition scaled with the extent of disorder created by laser irradiation. The consistent broadening of the d–d transition with irradiation indicates enhanced coupling between crystal field excitations and continuum states above the gap. These results are consistent with observed asymmetry in Raman modes and the Gaussian-like nature of excitonic spectral line shapes of optical absorption spectra with laser irradiation. Thus, we demonstrated a new way to probe the electron–exciton interactions in terms of crystal field transitions and excitonic line shapes in highly correlated systems. Additionally, the present work provides crucial information regarding lattice disordering in polycrystalline PrFeO3 with irradiation and may have significant implications for caution in using this material in extremely high radiation environments at room temperature. The results are further supported with a first-principle calculation carried out using density functional theory. Highlights: A completely new way was demonstrated to probe the electron/exciton interactions in terms of crystal field transitions and excitonic line shapes. The scaling of el-phonon coupling is consistent with asymmetry observed in Raman modes and Gaussian nature of excitonic shapes with irradiation. A detailed investigation of d-d transitions on pure and irradiated PrFeO3 was performed experimentally and using theoretical calculations.